1984
DOI: 10.1159/000176849
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein Cholesterol and Apoprotein A1 in Healthy Volunteers during Long-Term Moderate Alcohol Intake

Abstract: Moderate alcohol consumption is associated with lower cardiovascular mortality. The effect of moderate alcohol intake during 5 weeks on lipoproteins, especially on the high density lipoprotein (HDL) cholesterol total (of which the levels are inversely predictive of coronary heart disease) and apoproteins A, A1 and B, was studied in 7 normal men. HDL cholesterol total appreciated by the heparin manganese precipitation method and phosphortungstate magnesium method increased (p < 0.01) during alcohol consumption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…However, plasma triacylglycerol was unaffected by the wine when the meal was followed by a 15 h fasting period. This finding is in accordance with some long-term feeding studies which have failed to find any effect of moderate regular alcohol consumption on fasting plasma triacylglycerols in normal subjects (Hartung et al 1983;Couzigou et al 1984;Crouse & Grundy, 1984;McConnell et al 1997). However, recent meta-analysis of thirty-five human intervention studies with >6 d of alcohol administration revealed that alcohol consumption increased plasma triacylglycerol (Rimm et al 1999).…”
Section: Plasma Triacylglycerolsupporting
confidence: 87%
“…However, plasma triacylglycerol was unaffected by the wine when the meal was followed by a 15 h fasting period. This finding is in accordance with some long-term feeding studies which have failed to find any effect of moderate regular alcohol consumption on fasting plasma triacylglycerols in normal subjects (Hartung et al 1983;Couzigou et al 1984;Crouse & Grundy, 1984;McConnell et al 1997). However, recent meta-analysis of thirty-five human intervention studies with >6 d of alcohol administration revealed that alcohol consumption increased plasma triacylglycerol (Rimm et al 1999).…”
Section: Plasma Triacylglycerolsupporting
confidence: 87%
“…Although the crossover dietary trial was carried out on a small number of normolipidaemic healthy subjects, it confirms the modifications in plasma concentrations of HDLcholesterol, apoAI and apoAII under the effect of moderate alcohol consumption. Indeed, many studies have observed an increase in these parameters, either in chronic alcoholic [2,22] or in healthy volunteer subjects [23][24][25][26]. These results confirm those of previous studies, which have shown that the response of apoAII to alcohol was higher than that of apoAI in intemperate [27] as well as in normal subjects who received 60 g per day of alcohol [28].…”
Section: Discussionsupporting
confidence: 88%
“…Table 1 outlines the characteristics of the 63 included studies, totalling 1686 participants (1049 men and 625 women; one study of 12 participants did not indicate sex) 2021 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 Thirty six of the 63 (57%) studies included only men, eight (12.7%) included only women, and 19 (30%) included both. Thirty six studies used a crossover design and 24 used a before and after design, whereas three were parallel arm controlled trials.…”
Section: Resultsmentioning
confidence: 99%